2012
DOI: 10.1088/0004-637x/762/1/59
|View full text |Cite
|
Sign up to set email alerts
|

HerMES: CANDIDATE GRAVITATIONALLY LENSED GALAXIES AND LENSING STATISTICS AT SUBMILLIMETER WAVELENGTHS

Abstract: We present a list of 13 candidate gravitationally lensed submillimeter galaxies (SMGs) from 95 deg 2 of the Herschel Multi-tiered Extragalactic Survey, a surface density of 0.14 ± 0.04 deg −2. The selected sources have 500 μm flux densities (S 500) greater than 100 mJy. Gravitational lensing is confirmed by follow-up observations in 9 of the 13 systems (70%), and the lensing status of the four remaining sources is undetermined. We also present a supplementary sample of 29 (0.31 ± 0.06 deg −2) gravitationally l… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

15
230
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 177 publications
(247 citation statements)
references
References 151 publications
15
230
2
Order By: Relevance
“…Once corrected for magnification, the source has an intrinsic luminosity consistent with a ULIRG at z ∼ 2 with a SFR of around 200 M /year. The observed flux density at 500 µm of 325 mJy (Ivison et al, 2010d) puts this source among the brightest of all the lensed DSFGs discussed in the literature with Herschel-Spire Wardlow et al, 2013;Harris et al, 2012). Moreover, the high magnification of 32, compared to a magnification of about 10 for most lensed DSFGs found with Herschel , which are for galaxy-galaxy lenses, also more prone to differential lensing uncertainties), allows spatial resolution down to 100 parcsec scales within the galaxy.…”
Section: Smm J2135-0102: the Cosmic Eyelashmentioning
confidence: 78%
See 4 more Smart Citations
“…Once corrected for magnification, the source has an intrinsic luminosity consistent with a ULIRG at z ∼ 2 with a SFR of around 200 M /year. The observed flux density at 500 µm of 325 mJy (Ivison et al, 2010d) puts this source among the brightest of all the lensed DSFGs discussed in the literature with Herschel-Spire Wardlow et al, 2013;Harris et al, 2012). Moreover, the high magnification of 32, compared to a magnification of about 10 for most lensed DSFGs found with Herschel , which are for galaxy-galaxy lenses, also more prone to differential lensing uncertainties), allows spatial resolution down to 100 parcsec scales within the galaxy.…”
Section: Smm J2135-0102: the Cosmic Eyelashmentioning
confidence: 78%
“…However due to small sample size it was not possible to conclusively establish whether all of the extragalactic sources with S 500 > 100 mJy are gravitationally lensed or whether there are intrinsically luminous, but possibly rare, DSFGs at such high flux densities. With 13 DSFGs with S 500 > 100 mJy, Wardlow et al (2013) addressed the same issue and found >93% of the sample was confirmed to be gravitational lensed DSFGs implying <7% of the sources would be intrinsically bright. At z > 1, the non-lensed sources would have luminosities with L > 10 13 L (HyLIRGs).…”
Section: Lensed Dsfgsmentioning
confidence: 95%
See 3 more Smart Citations